Comparative Transcriptome Analysis of Key Genes and Pathways Activated in Response to Fat Deposition in Two Sheep Breeds With Distinct Tail Phenotype - Zhang, Wei; Xu, Mengsi; Wang, Juanjuan; Wang, Shiyin; Wang, Xinhua; Yang, Jingquan; Gao, Lei; Gan, Shangquan (Frontiers in Genetics, 2021)
Fat tail in sheep presents a valuable energy reserve that has historically facilitated adaptation to harsh environments. However, in modern intensive and semi-intensive sheep industry systems, breeds with leaner tails are preferred. In present study, RNA-Seq was applied to determine the transcriptome profiles of tail fat tissues in two Chinese sheep breeds with extreme fat-tail phenotype difference, followed by analysis of differentially expressed genes (DEGs) and their sequence variations. In total, 21,527 genes were detected, among which 3,965 displayed significant expression variations in tail fat tissues of the two sheep breeds, including 707 upregulated and 3,258 downregulated genes. Gene Ontology (GO) analysis disclosed that 198 DEGs were related to fat metabolism. In Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, the majority were significantly enriched in adipocytokine signaling, PPAR signaling, and metabolic pathways, with some genes being involved in multiple pathways. Among the 198 DEGs, 22 genes were markedly up or down regulated in tail fat tissue of Altay sheep, supporting their association with the fat tail trait of this breed. A total of 41,724 and 42,193 SNPs were detected in tail fat tissue transcriptomes of Altay and XFW sheep, respectively. The distribution of 7 SNPs in the coding regions of the 22 candidate genes was further investigated in three sheep populations with distinct tail types. In particular, the g.18167532 T/C mutation of ABCA1 and g.57036072 G/T mutation of SLC27A2 showed significantly different distributions and were closely associated with tail type. The present study provides transcriptomic evidence explaining the differences in fat- and thin-tailed sheep breeds and reveals numerous DEGs and SNPs associated with tail type. Our data provide a valuable theoretical basis for selection of lean sheep breeds.